2014
DOI: 10.20996/1819-6446-2014-10-2-195-202
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL AND MORPHOLOGICAL APPROACH TO DIAGNOSIS OF "IDIOPATHIC" ARRHYTHMIAS AND DILATED CARDIOMYOPATHY SYNDROME AS A BASIS FOR DIFFERENTIATED THERAPY. Part II (Treatment)

Abstract: Цель. Разработать комплексный клинико-морфологический подход к нозологической диагностике и лечению «идиопатических» аритмий (ИА) и синдрома дилатационной кардиомиопатии (ДКМП). Материал и методы. В основную группу включено 320 больных: 190 с ИА (117 женщин, ср. возраст 45,33±14,84 лет) и 130 с синдромом ДКМП (41 женщина, ср. возраст 46,89±12,50 лет), в контрольную-51 человек (пациенты с ишемической болезнью сердца, пороками, гипертрофической кардиомиопатии, которым выполнена операция на открытом сердце, здоро… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…This population group was most likely chosen due to high rates of incidence with infectious mononucleosis among people younger than 18 [27,29]. It was shown that children with heart rhythm disorders in their case history also more frequently had viral infections in it (infectious mononucleosis, chicken pox, rubella, or B19 parvovirus infection) than children without this pathology [38][39][40][41]. And there were cases when patients with heart rhythm disorders had genetic EBV materials detected in their serous pericardial effusion, endomyocardial tissue sampling, and venous blood [34,36,39,[41][42][43]; they also had IgM VCA in blood serum together with antibodies to antigens of working myocardium and conduction system [37,39,44,45].…”
Section: __________________________mentioning
confidence: 99%
“…This population group was most likely chosen due to high rates of incidence with infectious mononucleosis among people younger than 18 [27,29]. It was shown that children with heart rhythm disorders in their case history also more frequently had viral infections in it (infectious mononucleosis, chicken pox, rubella, or B19 parvovirus infection) than children without this pathology [38][39][40][41]. And there were cases when patients with heart rhythm disorders had genetic EBV materials detected in their serous pericardial effusion, endomyocardial tissue sampling, and venous blood [34,36,39,[41][42][43]; they also had IgM VCA in blood serum together with antibodies to antigens of working myocardium and conduction system [37,39,44,45].…”
Section: __________________________mentioning
confidence: 99%
“…Выбор данного контингента, по всей вероятности, был обусловлен высокими показателями заболеваемости инфекционным мононуклеозом среди лиц в возрасте до 18 лет [27,29]. Было показано, что у детей с нарушениями ритма сердца в анамнезе значительно чаще, чем у детей без данной патологии, имели место перенесенные вирусные инфекции (инфекционный мононуклеоз, ветряная оспа, краснуха, инфекция, вызванная парвовирусом В19) [38][39][40][41]. При этом у пациентов с нарушениями ритма сердца описаны случаи выявления генетического материала ВЭБ из серозного перикардиального выпота, эндомиокардиальных биоптатов, венозной крови [34,36,39,[41][42][43], а также IgM VCA в сыворотке крови при наличии аутоантител к антигенам рабочего миокарда и проводящей системы сердца [37,39,44,45].…”
unclassified